Building a Social Space through a Digital Library - Nafisah, Syifaun (Librarianship in Muslim Societies, 2023)
The development of the 4.0 revolution changed the library paradigm, shifting the types of libraries from conventional to digital libraries. The IFLA/UNESCO Manifesto for Digital Libraries officially declares a new paradigm shift in libraries. This manifesto allows libraries to save space by developing digital libraries to build social zones. A social zone is a place for human interaction in various activities. Interaction can occur in a physical or virtual context. This study aims to examine the potential for developing social space through the development of digital libraries. This study used a qualitative method with a field and literature study approach. This study conducted field data validation tests using triangulation techniques. Based on field research, libraries that have implemented digital libraries can save space usage. The room was originally for placing collection shelves; libraries can then use them to create public spaces. The creation of public space by the library is for activities that involve community participation, such as literacy. In addition, using space to build a co-working space also indirectly contributes to social interaction through discussion activities. The next task of the library is how the library can provide quality collections so that the library can make it a center of information.